2014
DOI: 10.1158/1078-0432.ccr-13-1993
|View full text |Cite
|
Sign up to set email alerts
|

IgG-Switched CLL Has a Distinct Immunogenetic Signature from the Common MD Variant: Ontogenetic Implications

Abstract: Purpose: Immunoglobulin G-switched chronic lymphocytic leukemia (G-CLL) is a rare variant of CLL, whose origin and ontogenetic relationship to the common IgM/IgD (MD-CLL) variant remains undefined. Here, we sought for clues about the ontogeny of G-CLL versus MD-CLL by profiling the relevant IG gene repertoires.Experimental Design: Using purpose-built bioinformatics methods, we performed detailed immunogenetic profiling of a multinational CLL cohort comprising 1,256 cases, of which 1,087 and 169 expressed IG mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
3
24
0
3
Order By: Relevance
“…34,35). A recent study of 169 IgG þ CLL cases from our joint cohort revealed that G-CLL exhibits an overall different immunogenetic signature from MD-CLL, even when restricting the comparison to cases with mutated BcR IGs (36). A significant proportion (18%) of this rare subgroup was found to consist of just two major CLL subsets, namely subsets #4 and #8.…”
Section: Bcr Signaling Capacitymentioning
confidence: 82%
See 1 more Smart Citation
“…34,35). A recent study of 169 IgG þ CLL cases from our joint cohort revealed that G-CLL exhibits an overall different immunogenetic signature from MD-CLL, even when restricting the comparison to cases with mutated BcR IGs (36). A significant proportion (18%) of this rare subgroup was found to consist of just two major CLL subsets, namely subsets #4 and #8.…”
Section: Bcr Signaling Capacitymentioning
confidence: 82%
“…CLL subset #4 (IGHV4-34/IGKV2-30) is considered to bear an inherently autoreactive BcR IG, which is effectively edited by the SHMs in critical positions (19). This may well be in line with the particularly indolent clinical course followed by these patients with CLL (14,36). At the other end of the spectrum, unmutated subset #8 (IGHV4-39/IGKV1(D)-39) carries a BcR IG with a conspicuously broad antigen reactivity profile, perhaps underlying clinical aggressiveness and risk of transformation to high-grade lymphoma (18).…”
Section: Bcr Signaling Capacitymentioning
confidence: 98%
“…We also investigated patients with CLL carrying non-subset BcR IG rearrangements, so as not to disregard the possibility of identifying T-cell immunogenetic features that are ubiquitous in CLL, irrespective of the particular IG receptor that is expressed. Our cohort was intentionally biased towards subset #4, where ample evidence suggests ongoing interactions with the selecting antigen (33)(34)(35)(36). For this reason, we also performed longitudinal immunoprofiling of five subset #4 patients, aiming to explore the possibility of clonal drift.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the low frequency of CLL cases with switched immunoglobulin (IG) in their B-cell receptors (BcR), this finding is highly suggestive of a particular immunopathogenetic process in this patient subgroup. 8 This claim was further supported by the remarkable bias to lambda light chain expression in this particular cytogenetic subgroup [22 of 32 cases (69%) with available data], raising the intriguing possibility that the respective clonogenic progenitors may have been subject to light chain receptor editing. All but one +12+19 CLL case with available information (47 of 48, 98%) carried immunoglobulin heavy variable (IGHV) genes impacted to some degree by somatic hypermutation (SHM), leading to IGHV genes with less than 100% germline identity.…”
mentioning
confidence: 90%
“…Panagiotis Baliakas, 1 Anna Puiggros, 2,3 Aliki Xochelli, 1,4 Lesley-Ann Sutton, 1 Florence Nguyen-Khac, 5 Anne Gardiner, 6 Karla Plevova, 7 Eva Minga, 4 Anastasia Hadzidimitriou,4 Renata Walewska, 6 Helen McCarthy, 6 Margarita Ortega, 8 Rosa Collado, 9 Teresa González, 10 Isabel Granada, 11 Elisa Luño, 12 Jana Kotašková, 7 Theodoros Moysiadis, 4 Zadie Davis, 6 Niki Stavroyianni, 13 Achilles Anagnostopoulos, 13 Jonathan C. Strefford, 14 Sarka Pospisilova, 7 Frederic Davi, 5 Anastasia Athanasiadou, 13 Richard Rosenquist, 1 David Oscier, 6 Blanca Espinet, 2,3 Figure 2. Kaplan-Meier curves for overall survival (OS).…”
mentioning
confidence: 99%